"Music Helps a West Papuan Feeling": West Papuan Musicians Mobilizing Affect and Communitas in Melbourne - Salay, Sebastian (The Contemporary Pacific, 2024)
Music making is an everyday activity for many people in the West Papuan community in Melbourne, Australia. The music they make negotiates the complex cultural and political dimensions implied by the term "West Papua"; the identity is especially complex for people living apart from the region itself. West Papua, the western half of the island of New Guinea, is the site of ongoing conflict and occupation. Resistance to Indonesian administration of the region is carried out by several loosely organized independence movements, which emphasize West Papuan cultural and political identity. According to Adam, a musician and regular presenter on the Voice of West Papua radio show, advocates for independence often use "music as a weapon."